The Influence of Interactive Learning Media on Students English Learning Outcomes in the Digital Era - Tiansi Tiansi; Marisa Marisa; Kurnia Febianti (Lembag, 2026)
The development of information and communication technology has significantly transformed the field of education. Teachers no longer depend only on lectures to deliver learning materials but also use various learning media to improve the effectiveness of the teaching and learning process. One of the most widely used innovations is interactive learning media, which combines text, images, audio, video, and other interactive features to support student learning. Interactive learning media can create a more engaging and enjoyable learning environment. Through this media, students actively participate in learning activities rather than simply receiving information passively. As a result, their attention, motivation, and understanding of the learning materials can improve. However, low student learning outcomes remain a challenge in education. Limited student involvement in the learning process often affects their ability to understand lessons and achieve learning objectives. Previous studies have indicated that interactive learning media can enhance both the quality of learning and student achievement. Therefore, examining the influence of interactive learning media on student learning outcomes is important to support the development of more effective, innovative, and technology-based learning processes in the digital era.